Analisis Akurasi Dan Dampak Kebijakan Originalitas Tugas Mahasiswa : Studi Kasus UIN Sumatera Utara Prodi Sistem Informasi - Much Nur Syams Simaja; Muhammad Irwan Padli Nasution (CV. Multi Kreasi Media, 2026)
In the classroom, rules regarding writing authenticity often sound simple—do not copy, cite sources—yet in practice, they are rarely straightforward. This case study captures how assignment originality screening was conducted in a single class at UIN Sumatera Utara (n=33) over a three-week period, during which the lecturer combined detection tools (similarity matching/AI) with manual verification and structured feedback. We collected policy documents, examination results from two manuscript versions (pre- and post-revision), responses to an 11-item Likert questionnaire, open-ended comments, and conducted brief interviews with the lecturer and several students. Quantitative analysis presents per-item summaries, 95% confidence intervals, thematic subscales, and composite score distributions; qualitative analysis synthesizes recurring themes from comments and interviews, specifically focusing on rule clarity, perceived fairness, and identifying what genuinely assists students when revising their writing. The results indicate a neutral-to-positive attitude toward the process (composite mean ≈ 3.47), peaking at the item regarding